Leveraging Augmented Reality (AR) to Enhance Reading Skills in Language Learning (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
Augmented Reality (AR) integrates digital information with the physical world, creating immersive and interactive learning experiences. This article explores the use of AR to enhance reading skills in language learners. By overlaying digital content onto physical texts, AR can provide contextual support, interactive elements, and engaging visuals, significantly improving learners' reading comprehension and overall language proficiency. This article examines the theoretical foundations, benefits, and practical strategies for integrating AR into reading instruction. Through analysis and case studies, we demonstrate how AR can effectively enhance learners' reading skills and support their language development.